miR-1266-3p Suppresses Epithelial-Mesenchymal Transition in Colon Cancer by Targeting P4HA3 - Hailang Zhou; Shu Huang; Changjiang Shao; Junwei Zou; Aijun Zhou; Jiufeng Yu; Chunfang Xu (Analytical Cellular Pathology)
Numerous studies have been conducted to demonstrate that miRNA is strongly related to colon cancer progression. Nevertheless, there are few studies regarding the function for miR-1266-3p in colon cancer, and the molecular mechanism remains poorly know. Our study was designed to examine the level of miR-1266-3p expression among the colon cancer tissue and cell and to study the role and regulatory mechanism for miR-1266-3p among colon cancer’s malignant biologic behavior. First, we found that miR-1266-3p expression was distinctly lower in colonic carcinoma tissues and cells than in nontumor ones, and the prognosis of low miR-1266-3p patients was distinctly worse than that of high miR-1266-3p patients. Second, we predicted that the target gene of miR-1266-3p was prolyl 4-hydroxylase subunit alpha 3 (P4HA3) through bioinformatics, and the targeting relationship between the two was verified by a dual luciferase assay report. Furthermore, miR-1266-3p inhibited the growth and metastasis of colon cancer in vitro as well as in vivo, and this effect could be alleviated by overexpressing P4HA3. Even more importantly, our study demonstrated that miR-1266-3p inhibited epithelial-mesenchymal transition (EMT) by targeting P4HA3. In conclusion, miR-1266-3p could inhibit growth, metastasis, and EMT in colon cancer by targeting P4HA3. Our discoveries might offer a novel target for colon cancer diagnosis and treatment.